Immunohistochemical Localization of Feline Immunodeficiency Virus Using Native Species Antibodies - Rogers, Arlin B. (American Society for Investigative Pathology, 2002)
Feline immunodeficiency virus (FIV) is the feline analog of human immunodeficiency virus and a small animal model of human acquired immune deficiency syndrome (AIDS). We sought to identify early in vivo target cells in cats infected with clade B or C FIV. In tissues, however, neither mouse monoclonal nor rabbit polyclonal antibodies suitably detected FIV because of either insensitivity or lack of specificity. We therefore developed an immunohistochemical protocol using high-antibody-titer serum from cats chronically infected with FIV(Petaluma). Native species anti-FIV antibodies were labeled with biotinylated protein A before placement on tissues, and downstream signal was tyramide-amplified. This method revealed many productively infected cells in bone marrow, lymph node, thymus, mucosal-associated lymphoid tissue, and spleen, but few such cells in liver and none in kidney or brain. Concurrent labeling for virus and cell phenotype revealed that antigen-bearing populations were primarily T lymphocytes but included macrophages and dendritic cells. Our results demonstrate that FIV: 1) expands rapidly in T cells, 2) targets long-lived reservoir populations, and 3) is replicatively quiescent in brain at 3 weeks after infection. Use of native species antibodies for immunohistochemical detection of infectious antigens has application to other settings in which xenotypic (eg, mouse and rabbit) antibody sources are inadequate or unavailable.